2021
DOI: 10.1016/j.amp.2021.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Enjeux psychiques et psychopathologiques des croyances conspirationnistes : de la crise sanitaire du COVID-19 à la crise existentielle

Abstract: La recherche sur les théories du complot connaît un engouement grandissant ces dernières années. Les travaux sont issus de diverses disciplines du champ des sciences humaines. Ils mettent notamment en évidence que l’adhésion aux croyances conspirationnistes connaît un rebond à chaque moment de « crise ». La crise sanitaire que nous traversons n’échappe pas à la règle : la pandémie de COVID-19 se double d’une infodémie , selon le mot de Tedros Ghebreyesus, Directeur Général de l’Organisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A proposal for future investigations, derived from the results of this study, is to go deep into elements related to the current infodemic (conspiracy theories or another kind of misinformation). As argued by Poupart and Bouscail (2021), this pandemic demonstrates that the spread of false news and support to conspiracy theories is not marginal, which could bring potentially negative impacts in terms of public health. Other studies have highlighted the risks to public health that a segment of the population supports the fake news and misinformation circulating through social media (Cuan-Baltazar et al, 2020;Van Bavel et al, 2020).…”
Section: Conspiracy Theories Misinformation and Communicationmentioning
confidence: 96%
See 2 more Smart Citations
“…A proposal for future investigations, derived from the results of this study, is to go deep into elements related to the current infodemic (conspiracy theories or another kind of misinformation). As argued by Poupart and Bouscail (2021), this pandemic demonstrates that the spread of false news and support to conspiracy theories is not marginal, which could bring potentially negative impacts in terms of public health. Other studies have highlighted the risks to public health that a segment of the population supports the fake news and misinformation circulating through social media (Cuan-Baltazar et al, 2020;Van Bavel et al, 2020).…”
Section: Conspiracy Theories Misinformation and Communicationmentioning
confidence: 96%
“…Recent research has shown that there has been a significant increase in the belief of conspiracy theories during the COVID-19 pandemic, especially those connected to COVID-19 or anti-vaccination (Leibovitz et al, 2021 ). During crisis time, with higher levels of stress, anxiety, and uncertainty, conspiracy theories seem to flourish, affecting how individuals behave (Constantinou et al, 2021 ; Douglas, 2021 ; Poupart and Bouscail, 2021 ). In this crisis context, conspiracy theories or narratives play a role in finding meaning, fighting fears, and reducing anxiety (Ali, 2020 ; Schippers, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases when the object is truth, almightiness takes the form of infallibility. Fetishism thus provides a potential psychological mechanism underlying many versions of explicitly “anti-vax” conspiracy theory speech, which frequently displays a conviction of absolute certainty; it also accounts for the oft-highlighted connection ( Poupart and Bouscail, 2021 ), and even prediction, of VS or AV attitudes in the presence of prior adhesion to conspiracy theories ( Al-Jayyousi et al, 2021 ; Nazlı et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%